Characterization of the patients with kwashiorkor attended in the therapeutic feeding center in Al-Sadaqa Teaching Hospital, Aden, Yemen - Hussein Badi, Mohammed Ali; García Triana, Bárbara Elena (Revista Habanera de Ciencias Médicas, 2015)
Introduction: Each year nine million children under age five years die. Malnutrition contributes to one-third of these deaths, being the mortality rate for kwashiorkor much higher than for marasmus. Objective: To characterize the patients with kwashiorkor attended in the therapeutic feeding center in Al-Sadaqa Teaching Hospital, Aden, Yemen. Material and methods: This cross-sectional study was performed on 95 kwashiorkor children (45 males and 50 females) under 5 years of age, 2010-2013. Data was collected from the charts of children at the therapeutic feeding center in Al-Sadaqa Teaching Hospital, Aden, Yemen. Kwashiorkor was defined as a very low weight for height with edema. Results: A total of 1978 children under 5 years were diagnosed with malnutrition in this feeding center during the period of study. The kwashiorkor cases were 95 (4.8%). A high percentage of kwashiorkor (92.6%) was found in children ≤4 years old. Although female cases were higher than male cases (52.6% versus 47.4%), the difference was not statistically significant. Around 50.5% of kwashiorkor cases were from Aden city. The proportion of patients who were cured (72.6%) was markedly higher than the proportions for other groups, being the death rate 8.4%; there was a significant relationship between kwashiorkor and outcome among studied children. Conclusions: The prevalence of kwashiorkor at the therapeutic feeding center in Al-Sadaqa Teaching Hospital is 4.8%, which is higher for ≤4 years old children. It is recommended to promote the knowledge and health education and to improve the economic and cultural conditions of families. Keywords: kwashiorkor, prevalence, malnutrition, children, Al-Sadaqa Therapeutic Feeding Center, Aden RESUMEN Introducción: Cada año mueren nueve millones de niños menores de cinco años. La malnutrición contribuye a un tercio de estas muertes, siendo el porcentaje de mortalidad para el kwashiorkor muy superior a la del marasmo. Objetivo: Caracterizar a los pacientes con kwashiorkor atendidos en el centro terapéutico de alimentación del Hospital Docente “Al-Sadaqa”, Adén, Yemen. Material y métodos: Este estudio de corte transversal se realizó en 95 niños con kwashiorkor (45 niños y 50 niñas) menores de 5 años, 2010-2013. Los datos se recogieron de las historias clínicas en el centro terapéutico de alimentación del Hospital Docente “Al-Sadaqa”, Adén, Yemen. El se definió como muy bajo peso para la talla con edema. Resultados: Un total of 1978 niños menores de 5 años fueron diagnosticados con malnutrición en esta unidad durante el periodo de estudio. Los casos de kwashiorkor fueron 95 (4.8%). Se encontró un alto porcentaje de kwashiorkor (92.6%) en niños ≤4 años. Aunque el número de casos en las hembras fue mayor que en los varones (52.6% versus 47.4%), la diferencia no fue estadísticamente significativa. Alrededor del 50.5% de los casos de kwashiorkor fueron de la ciudad de Adén. La proporción de pacientes curados (72.6%) fue marcadamente superior a la de otros grupos, resultando fallecidos el 8.4%. Conclusiones: El porcentaje de kwashiorkor en el centro terapéutico de alimentación del Hospital Docente “Al-Sadaqa” es de 4.8%, la cual es mayor para los niños de 4 o menos años de edad. Se recomienda promover el conocimiento y la educación para la salud y mejorar las condiciones económicas y culturales de las familias. Palabras clave: kwashiorkor, prevalencia, malnutrición, niños, centro terapéutico de alimentación “Al-Sadaqa”, Adén